2010
DOI: 10.24908/pceea.v0i0.3087
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Creative Concept Generation by Engineering Students with Biomimetic Design

Abstract: Biomimetic design uses ideas from biology as inspiration for design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, when asked which abstraction technique they used from a list developed from the literature review, including functional decomposition [28,[30][31][32], the function-means tree [33], C-K modelling [34,35], checklist of key questions [36], the 'abstracting design principles' step of Biomimicry Thinking [10], causal relationship template [37], structure-behaviour-function [38], what-why-how template [39], SR.BID or the Four Box Method [40], DANE structured descriptions [41], the SAPPhIRE model of causality [42], and BioTRIZ [66], my own process of analysis and interpretation, none of the above, and other, 75% (n = 43) of those that used physical models also reported that they use 'my own process', a statistically significant correlation, X 2 (12) = 8.876, p = 0.003, Cramer's V = 0.181. Additional significant correlations between the use of physical models and 'checklist of key questions' and 'structure-function-behavior' as abstraction techniques were found, though with less prevalence.…”
Section: Statistical Results On the Use Of Prototyping Among Biomimicry Practitionersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when asked which abstraction technique they used from a list developed from the literature review, including functional decomposition [28,[30][31][32], the function-means tree [33], C-K modelling [34,35], checklist of key questions [36], the 'abstracting design principles' step of Biomimicry Thinking [10], causal relationship template [37], structure-behaviour-function [38], what-why-how template [39], SR.BID or the Four Box Method [40], DANE structured descriptions [41], the SAPPhIRE model of causality [42], and BioTRIZ [66], my own process of analysis and interpretation, none of the above, and other, 75% (n = 43) of those that used physical models also reported that they use 'my own process', a statistically significant correlation, X 2 (12) = 8.876, p = 0.003, Cramer's V = 0.181. Additional significant correlations between the use of physical models and 'checklist of key questions' and 'structure-function-behavior' as abstraction techniques were found, though with less prevalence.…”
Section: Statistical Results On the Use Of Prototyping Among Biomimicry Practitionersmentioning
confidence: 99%
“…Much of the research and databases of biological mechanisms developed to date provide insight into techniques for abstraction and transfer and are largely based on semantics and systematic language analysis. Various techniques are currently described in the literature, including functional decomposition [28,[30][31][32], the function-means tree [33], concept-knowledge (C-K) modelling [34,35], checklist of key questions [36], the 'abstracting design principles' step of Biomimicry Thinking [10], causal relationship template [37], structure-behaviour-function (SBF) [38], what-why-how template [39], structured representations for biologically inspired design (SR.BID) or the Four Box Method [40], Design Analogy to Nature Engine (DANE) structured descriptions [41], the SAPPhIRE model of causality [42], as well as terminology supports such as analogical categories [5], the Engineering to Biology Thesaurus [43], and the Biomimicry Functional Taxonomy [10]. The strength of many of these approaches is in standardizing the process for isolating and identifying key variables of the biological mechanism and in some cases subsequently populating a rich, searchable database and/or to provide guidance on how to translate biological information to design and engineering language.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, bioinspired design (BID) has been acknowledged to increase creativity and innovation (Cheong and Shu 2010). Nowadays, bioinspired design (BID) has been acknowledged to increase creativity and innovation (Cheong and Shu 2010).…”
Section: Introductionmentioning
confidence: 99%